2016
DOI: 10.1124/jpet.116.233551
|View full text |Cite
|
Sign up to set email alerts
|

New Morphine Analogs Produce Peripheral Antinociception within a Certain Dose Range of Their Systemic Administration

Abstract: Growing data support peripheral opioid antinociceptive effects, particularly in inflammatory pain models. Here, we examined the antinociceptive effects of subcutaneously administered, recently synthesized 14-O-methylmorphine-6-O-sulfate (14-O-MeM6SU) compared with morphine-6-O-sulfate (M6SU) in a rat model of inflammatory pain induced by an injection of complete Freund's adjuvant and in a mouse model of visceral pain evoked by acetic acid. Subcutaneous doses of 14-O-MeM6SU and M6SU up to 126 and 547 nmol/kg, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 39 publications
5
30
0
Order By: Relevance
“…Similar results were reported for morphine-6-O-sulphate in several tests: the tail flick test, chronic constriction nerve injury hyperalgesia and allodynia, and formalin test [23]. On the contrary, the doses of morphine-6-O-sulphate required to alleviate visceral pain in acetic acid-induced writhing in mice were equal to doses that affect GI peristalsis [24]. Morphiceptin derivatives with β2-or β3-amino acids synthesized by Gach et al [21]: peptide 2 and peptide 4 exerted strong antinociceptive action in acetic acid writhing test in mice, the effect was comparable to morphiceptin (0.1 mg/kg, ip).…”
Section: Discussionsupporting
confidence: 81%
“…Similar results were reported for morphine-6-O-sulphate in several tests: the tail flick test, chronic constriction nerve injury hyperalgesia and allodynia, and formalin test [23]. On the contrary, the doses of morphine-6-O-sulphate required to alleviate visceral pain in acetic acid-induced writhing in mice were equal to doses that affect GI peristalsis [24]. Morphiceptin derivatives with β2-or β3-amino acids synthesized by Gach et al [21]: peptide 2 and peptide 4 exerted strong antinociceptive action in acetic acid writhing test in mice, the effect was comparable to morphiceptin (0.1 mg/kg, ip).…”
Section: Discussionsupporting
confidence: 81%
“…It is well known, that partial agonists show lower agonist activity than the higher efficacy opioid agonists when the MOR reserve is decreased [40]. Additionally, this pain model is widely used in opioid research to assess the contribution of the peripheral opioid receptors to antinociception [5,44]. Here we found that systemic administration of both 14-OMeC6SU and C6SU abolished the reduced pain threshold of the inflamed paws, indicating the antihyperalgesic effects of the test compounds.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, pharmacological evidence has shown that opioids are also capable to produce antinociception by the activation of opioid receptors reside outside the central nervous system [4][5][6][7][8][9][10]. Indeed, opioid agonists that have been reported to induce peripheral antinociception display a prerequisite physiochemical property, a limited central nervous system (CNS) penetration [4,5,7]. Thus, over the last four decades many opioid research groups have undertaken the task of synthesis and pharmacological characterization of opioid compounds with limited CNS penetration and thereby inducing antinociception by activating opioid receptors at the periphery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since morphine derivatives possess a basic tertiary amino group, these compounds are zwitterionic at physiological pH values. Thus, these sulfate esters cannot cross the blood‐brain barrier, and consequently are good candidates to develop peripheral analgesic drugs …”
Section: Metabolites Of Morphinementioning
confidence: 99%